Endobronchial involvement in Wegener's granulomatosis. - Amin, R. (BMJ Group, 1983)
Right middle lobe collapse as a result of endobronchial involvement with Wegener's granulomatosis is reported in a 60-year-old woman. A review of the literature has revealed 6 cases of lobar collapse, only 2 of which had endobronchial disease.